Developing islamic religious and moral education academic assessment instrument for students with intellectual disability - Syamsiah Syamsiah; Usman Bafadal; Mustafa Mustafa; Purwaka Hadi (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2022)
The purpose of this study was to determine the validity and practicality of the newly developed Islamic Religious and Moral Education Education academic assessment instrument for students with intellectual disability at SLBN (State Special School) 1 Makassar). This study was conducted by using research and development model. Research and development is a study aiming to produce a certain product or improve an existing product. The research and development model applied in this study was the one proposed by Borg & Gall. Purposive sampling was implemented to obtain the research subject. The data were analyzed using qualitative descriptive and quantitative descriptive method. The results of data analysis showed that the average percentage of students’ achievement level is in very practical and very valid category. The conclusion of this study is that the developed academic assessment instrument is feasible to be used as a reference to measure the students with intellectual disability’s independence level development regarding with their ability to cary out their daily worship activities.